ARTIFICIAL INTELLIGENCE IN OPHTHALMOLOGY: CHALLENGES AND READINESS IN INDONESIA - Asnhy Anggun Dien Putri; Ivana Beatrice Alberta; Fredy Ciputra (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2023)
Introduction and Objective: Artificial Intelligence (AI) has been increasingly used in various fields of medicine. It involves the development of algorithms and computer programs that can learn from and adapt to data, enabling machines to perform tasks without explicit human instructions. The ultimate goal of AI is to create machines that can think and reason like humans. AI has the potential to transform the field of ophthalmology, which leads to improved patient care. This study aims to examine the current state of AI in ophthalmology, the challenges facing its adoption in Indonesia, and the opportunities for growth and development in this field.Method: A literature search was conducted using PubMed, Google Scholar, and Proquest to identify relevant studies and reports related to AI in ophthalmology.Result: AI in ophthalmology has been studied extensively in the field of screening, diagnosis, management, and predicting outcomes. Some studies proved that AI has a relatively high accuracy in diagnosing certain eye diseases, as demonstrated by its high sensitivity and specificity. However, high accuracy does not necessarily mean that AI is ready for clinical practice, especially in Indonesia. Several challenges include the risk of bias, the absence of standard assessment methods for AI, inadequate infrastructure and regulation, ethics, and sociocultural aspects.Conclusion: AI has the potential to revolutionize the ophthalmology field in Indonesia, leading to better patient outcomes and more efficient healthcare systems.Keywords             : Artificial intelligence, challenges, Indonesia, ophthalmology